Reply to ‘Non-freezing cold injury? a multi-faceted syndrome’ - Vale, T; Symmonds, M; Polydefkis, M; Byrnes, K; Rice, A; Themistocleous, A; Bennett, D (Oxford University Press, 2018)
We thank Eglin et al for their thoughtful commentary on our manuscript, in which we undertook the first detailed neurological assessment of persistent symptoms following non-freezing cold injury. Whilst we stress that sensory neuropathy is one core feature of NFCI we do not want to give the impression that vascular factors may not play a role. In fact, given the intimate relationship between peripheral neurons and blood vessels in the neurovascular unit, it would be a surprise if vascular changes were not observed.